Concept-Based Oral Systemic Manifestation of Type 2 Diabetes - Georgia Dounis (Association of American Medical Colleges, 2014)
Abstract Type 2 diabetes is the fastest-growing chronic condition in the nation and the seventh leading cause of death. In older adults this disease and associated comorbidities affects multi-organ systems, resulting in numerous oral-systemic health care needs that require management from multiple health care providers. Oral disease and type 2 diabetes are both chronic inflammatory diseases with bidirectional relationship that share common risk factors and require comprehensive, complementary, coordinated, delivery of health care services. Modern advancements are enabling older adults to retaining their natural dentition with a decline in edentulism. The purpose of this nontraditional patient-centered module is to examine the myriad of issues surrounding the optimum management and disease prevention of older adults with type 2 diabetes in acute health care settings. Instructional material are developed for diverse health care professionals to jointly address oral manifestation of a chronic systemic condition (type 2 diabetes) that increases risk to oral disease. The goals of this interprofessional training module is the collaborative management of the oral-systemic manifestations of type 2 diabetes as well as define the role of the health care professionals as both a discipline expert and member of the team.